A reconfigurable millimeter-wave wideband low-noise amplifier in 55-nm CMOS. (September 2022) - Zhang, Wei; Deng, Dongqin; Wan, Jialong; Wang, Hao; Chang, Sheng; Huang, Qijun; He, Jin
Abstract: This paper presents a dual-wideband millimeter-wave (mm-wave) low-noise amplifier (LNA) that can be reconfigured covering dual bandwidths of 22.8–28.9 GHz and 23.2–29.5 GHz by RF-switched passive inductors for 5G applications. The reconfigurable LNA (RLNA) employs a three-stage cascode structure to enhance the gain and linearity effectively and has been designed and fabricated in 55-nm CMOS. With a switch voltage ( V s ) of 0 V, the RLNA achieves measured gain of 26.7 dB at the peak frequency ( f p ) of 24.7 GHz, gain of 23.7–26.7 dB and noise figure (NF) of 5.2–5.8 dB over 3-dB bandwidth from 22.8 to 28.9 GHz (6.1 GHz). While at V s of 1.2 V, the RLNA exhibits measured gain of 23.8 dB at the f p of 25.4 GHz, gain of 20.5–23.8 dB and NF of 5.8–6.3 dB across 3-dB bandwidth of 23.2–29.5 GHz (6.3 GHz). The chip including all testing pads occupies a die area of 0.7 × 0.55 mm 2, which consumes 25.2 mW from a voltage supply of 1.2 V.